(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Arabic Prose in India has been significantly enriched by various factors, including religious influence, the patronage of Muslim rulers and the establishment of numerous educational institutions. The existence of a large number of Arabic Madrassas all over India, where Arabic language and literature is being taught to the students and thus the Arabic language and literature became more attractive and enlivened. These institutions product many intellectuals and scholars whose written books not only spread out the network of Arabic language and literature all over the country, but also influenced the Arab word. Arabic is the youngest variety of Semitic groups of languages. This language originates a few centuries before the rise of Islam. Arabic is considered as the most sacred language by the people of Muslim Community, because it is the language of the Holy Qur’an and Hadith. The people of India started learning Arabic language not only to carry on the trade but also to focus the Islam. Thus, Arabic spread and flourished in India. The Holy Qur’an is the first great work of Arabic prose literature. Hadith is another source of Arabic prose literature, which provides the basic sources for the biography of prophet Muhammad (SAW). Literature is not limited by the collection of prose and poetry; it is included various purposes. Arabic prose is to open in brief among the subjects, Nahu, Sarf, Philosophy, scholastic, logic, fiqh etc. There are several Arabic prose writers in India, who flourished and developed Arabic prose literature there. Various famous Arabic Newspapers and Magazines published in India, among them; al Bayan, al Jamiyat, al Hilal, al Ba’as al Islami and al Rayed etc. are notable. By these Magazines, Newspapers and valuable works of distinguished writers, Arabic prose has been developed in India. In this discussion, we shall try to focus on the development of Arabic prose literature especially in India.